2012
DOI: 10.1088/0004-637x/753/1/40
|View full text |Cite
|
Sign up to set email alerts
|

How Many Ultra-High Energy Cosmic Rays Could We Expect From Centaurus A?

Abstract: The Pierre Auger Observatory has associated a few ultra high energy cosmic rays with the direction of Centaurus A. This source has been deeply studied in radio, infrared, X-ray and γ-rays (MeV-TeV) because it is the nearest radioloud active galactic nuclei. Its spectral energy distribution or spectrum shows two main peaks, the low energy peak, at an energy of 10 −2 eV, and the high energy peak, at about 150 keV. There is also a faint very high energy (E ≥ 100 GeV) γ-ray emission fully detected by the High Ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 50 publications
0
44
0
Order By: Relevance
“…Due to photo-disintegration of Fe nuclei by 170 KeV photons we expect a peak in the high energy gamma ray spectrum at 400M eV . In [36] the authors have used the low energy photon spectrum from [40] for calculating the high energy gamma ray flux from the lobes of Cen A, but the low energy photon spectrum given in [40] is observed from the core of Cen A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to photo-disintegration of Fe nuclei by 170 KeV photons we expect a peak in the high energy gamma ray spectrum at 400M eV . In [36] the authors have used the low energy photon spectrum from [40] for calculating the high energy gamma ray flux from the lobes of Cen A, but the low energy photon spectrum given in [40] is observed from the core of Cen A.…”
Section: Discussionmentioning
confidence: 99%
“…If the lower energy bound is 1 EeV then the estimated luminosity in the band of 1 EeV to 150 EeV is 5 × 10 40 erg/sec, which is below the bolometric luminosity 10 43 erg/sec of this source. Fraija et al [36] have explained the emission of gamma rays observed by HESS and the UHECR events observed by Pierre Auger with p − p interactions assuming the gamma ray emission is from the lobes of Cen A. They have shown that the scenario of p − γ interactions in their model is not consistent with the observational results.…”
Section: Introductionmentioning
confidence: 99%
“…Hadronic interactions within the extended lobes have been proposed to produce gamma-rays in the GeV -TeV energy range [75]. Assuming that CRs are described by a simple power law,…”
Section: A3 Hadronic Interactionsmentioning
confidence: 99%
“…Taking into account the proton distribution (Eq. 2.1) and the conservation of the photo pion flux (Atoyan & Dermer 2003;Fraija et al 2012b;Aharonian 2002) where the proportionality constant of pp interaction is…”
Section: Vhe Neutrino Expectation From Fr Imentioning
confidence: 99%